Binding of methyl orange or ethyl orange dyes by some dioxolane copolymers: Synthesis of the copolymers and thermodynamics of the dye-copolymer interactions - Ceylan, NN; Ilter, Z (Wiley, 2004)
The extent of binding of methyl orange or ethyl orange by (2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate (PDMMA), 2-hydroxyethyl methacrylate (HEMA), and vinyl-pyrrolidone (VPy) copolymers has been investigated by the equilibrium dialysis method. The dialysis experiments have been carried out in a Tris (hydroxy methyl) aminomethane buffer (pH = 7) and at the temperatures of 15, 25, and 35degreesC. The PDMMA-co-HEMA and PDMMA-co-VPy copolymers have been prepared in the laboratory by using the related monomers in different ratios. The synthesized products were analyzed by Fourier Transform-infrared spectroscopy (FTIR), proton nuclear magnetic resonance (H-1 NMR) spectroscopy, differential thermal analysis (DTA), and differential scanning calorimetry (DSC) techniques. The binding extent of the dyes by the copolymers was determined by ultraviolet (UV) absorbance measurements. The results indicate that the extent of binding is relatively higher for ethyl orange than that for methyl orange under identical conditions. The binding slightly decrease with increasing temperature, and it is accompanied with favorable free energy, and exothermic enthalpy change within the temperature range studied. (C) 2004 Wiley Periodicals, Inc.
Keywords: equilibrium dialysis; thermodynamics; 1,3-dioxalane; dye-binding